Anti-Fatigue Effects of Acute Red Ginseng Intake in Recovery from Repetitive Anaerobic Exercise - Seongeon KIM; Jooyoung KIM; Yongsoo LEE; Min Keun SEO; Dong Jun SUNG (Tehran University of Medical Sciences, 2016)
No Abstract